2018
DOI: 10.1088/1361-6560/aab1ee
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of EBT-XD and EBT3 radiochromic film dosimetry for photon and proton beams

Abstract: Recently, a new type of radiochromic film, the EBT-XD film, has been introduced for high dose radiotherapy. The EBT-XD film contains the same structure as the EBT3 film but has a slightly different composition and a thinner active layer. This study benchmarks the EBT-XD against EBT3 film for 6 MV and 10 MV photon beams, as well as for 97.4 MeV and 148.2 MeV proton beams and 15-100 kV x-rays. Dosimetric and film reading characteristics, such as post irradiation darkening, film orientation effect, lateral respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 39 publications
9
97
0
Order By: Relevance
“…Films were positioned at the center of the scanner using a template to ensure a reproducible orientation. Although a small response change with the orientation has been reported for the EBT‐XD film model compared to the EBT3 model, in this study, the films were scanned in portrait mode. Images were acquired in transmission mode with RGB colors, 16 bits per color channel, all color corrections turned off, and spatial resolution of 72 dpi (0.35 mm × 0.35 mm pixel size).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Films were positioned at the center of the scanner using a template to ensure a reproducible orientation. Although a small response change with the orientation has been reported for the EBT‐XD film model compared to the EBT3 model, in this study, the films were scanned in portrait mode. Images were acquired in transmission mode with RGB colors, 16 bits per color channel, all color corrections turned off, and spatial resolution of 72 dpi (0.35 mm × 0.35 mm pixel size).…”
Section: Methodsmentioning
confidence: 94%
“…The active layer of the EBT‐XD model is sandwiched between two matte polyester substrate each with 125 μm thickness, identical to that of the EBT3 model. There are several studies on the characterization and validation of the EBT‐XD films for radiotherapy dosimetry applications . These studies showed an improved performance of the EBT‐XD film over the EBT3 model for applications requiring doses greater than 10 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D dose distribution was determined using Gafchromic EBT3 films (Ashland Advanced Materials, Bridgewater, NJ, USA) in a solid water phantom (Gammex/Sun Nuclear Corporation, Melbourne, Australia). The film was scanned using an Epson V700 scanner (Epson, Nagano, Japan) 24 h after irradiation . The resulting dose distribution was convolved with a disc‐shaped convolution kernel with 1.2 mm diameter to mimic the active volume of a PTW 60017 DiodeE detector (PTW, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Further details about film handling and analysis can be obtained from previous results of our research group. 18,19,46 Besides the measurements with the homogeneous PMMA phantom, two heterogenous material configurations were investigated. Material (bone and tissue) slabs of 20 9 50 9 150 mm 3 were placed at the phantom entrance in two geometrical configurations: centrally and creating a lateral interface, see Fig.…”
Section: C2 Dose Distributionsmentioning
confidence: 99%
“…The energy-dependent response of Gafchromic EBT3 films makes their use for particle therapy more difficult compared to photon therapy. [16][17][18][19] For clinical proton beams, the dose obtained from films can be underestimated up to 20% in the Bragg peak region. 16,20,21 To correct for the LET quenching, several models are available in literature.…”
Section: Introductionmentioning
confidence: 99%